Favorable efficacy of glecaprevir plus pibrentasvir as salvage therapy for HCV failures to prior direct‐acting antivirals regimens. Issue 1 (3rd September 2018) - Akuta, Norio; Sezaki, Hitomi; Suzuki, Fumitaka; Fujiyama, Shunichiro; Kawamura, Yusuke; Hosaka, Tetsuya; Kobayashi, Masahiro; Kobayashi, Mariko; Saitoh, Satoshi; Suzuki, Yoshiyuki; Arase, Yasuji; Ikeda, Kenji; et al.
Abstract : In real‐world settings, not much information is probably available on the treatment efficacy of the combination of glecaprevir and pibrentasvir (G/P) as a salvage therapy in failures of prior direct‐acting antiviral (DAA) regimens. Especially, the evolution of NS5A resistance‐associated variants (RAVs) and treatment efficacy in patients who received G/P for failures of prior treatment more than once is unknown. Twenty patients, who were exposed to glecaprevir 300 mg/d and pibrentasvir 120 mg/d for 12 weeks in failures of prior DAAs regimens were evaluated for sustained virological response at 12 weeks after the end of treatment (SVR12). The overall rate of SVR12 was 100%, based on intention‐to‐treat analysis. Five patients infected with genotype 1b, who received G/P for failures of prior treatment more than once, were analyzed for the evolution of RAVs in NS5A region. All of the five patients exhibited SVR12, regardless of the numbers of times of prior treatment (more than once), prior treatment response (nonresponse), and fibrosis stage (FIB‐4 index ≥ 3.25). At the commencement of G/P, all five patients were detected with NS5A RAVs at the position of aa 93. Four patients, except for one, were detected with RAVs at both positions of aa 31 and aa 93 (double mutation). All patients could achieve SVR12 with G/P, regardless of the emergence of NS5A RAVs, accompanied by failure to prior NS5A regimens more than once. In conclusion, our study indicated that G/P was a potentially useful salvage treatment for patients who failed prior DAAs regimens more than once. Highlights: The overall rate of SVR12, with glecaprevir and pibrentasvir (G/P) as salvage therapy in failures to prior direct‐acting antivirals (DAAs) regimens, was 100%. All patients could achieve SVR12 with G/P, regardless of emergence of NS5A RAVs, accompanied by failure to prior NS5A regimens more than once. G/P was a potentially useful salvage treatment for patients who fail prior DAAs regimens more than once.